1969
DOI: 10.1002/1097-0142(196912)24:6<1301::aid-cncr2820240642>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer—Preoperative and postoperative radiation therapy

Abstract: Our goal is to develop new methods of breast cancer treatment that produce results better than those usually obtained in patients with operable breast cancer who have a radical mastectomy and patients with inoperable breast cancer who receive desultory and inadequate radiation therapy. We must examine our views “operable patients are curable” and “inoperable patients are incurable” in light of our actual results and recent changes in understanding of the mechanisms of failure to cure breast cancer by surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…''-William E. Powers, MD, Radiologist, in Cancer, 1969. 3 Before 1950, a survey showed that postoperative radiation therapy, which always meant post-radicalmastectomy radiation at that time, was being used in 37% of cases of breast cancer. 4 Patients who had been treated with radiation did not appear to have different survival outcomes than those who did not.…”
Section: S To 1960smentioning
confidence: 99%
“…''-William E. Powers, MD, Radiologist, in Cancer, 1969. 3 Before 1950, a survey showed that postoperative radiation therapy, which always meant post-radicalmastectomy radiation at that time, was being used in 37% of cases of breast cancer. 4 Patients who had been treated with radiation did not appear to have different survival outcomes than those who did not.…”
Section: S To 1960smentioning
confidence: 99%